Strength and Ductility of High-Strength SFRC Confined by Spirals and Hoops Constructed with Self-Compacting Concrete - Cholida, Nur Fithriani F.; Antonius; Rochim, Abdul (Engineering, Technology & Applied Science Research, 2026)
This paper presents the results of an experimental investigation of high-strength Steel Fiber-Reinforced Concrete (SFRC) with Self-Compacting Concrete (SCC) containing spiral and hoop reinforcement, which was subjected to axial compressive loading. Forty cylindrical concrete specimens, each with a diameter of 100 mm and a height of 200 mm, were used to evaluate the effectiveness of producing confined SFRC using SCC by examining several design parameters, including the type of confining reinforcement (spiral and hoop), fiber volume fraction (0%, 0.5%, and 1%), as well as the spacing and yield strength of the confining reinforcement. The experimental results revealed that closer spacing of transverse reinforcement or a higher volumetric ratio enhances the strength of confined concrete (K) and increases ductility, as measured by the Toughness Index (TI). An increase in fiber volume fraction in confined concrete reduces the value of K; however, the TI increases, particularly when the transverse reinforcement spacing equals the specimen diameter. Specimens with a water-to-cement ratio (w/c) of 0.34, reinforced with spiral confinement, achieved an optimum K value of 1.51 at a fiber volume fraction (vf) of 0%. Nevertheless, the highest ductility was observed in specimens with spiral confinement and a vf of 1%, giving a TI value of 0.84. For a w/c mix design of 0.55, the optimum K value was obtained with hoop reinforcement (K = 1.54). However, the optimum ductility occurred in specimens with spiral confinement and vf = 1%, resulting in a TI value of 0.87. A linear regression analysis of the experimental data indicates that the confinement effectiveness is 3.0.